A feminist introduction to romanticism - Fay, Elizabeth A., 1957- (Blackwell Publishers, 1998)
Elizabeth Fay's invaluable book addresses the reader in an immediate and direct manner to provide an unequaled introduction to the issues most important for feminist analyses of Romantic literature. In her opening chapter, Fay offers detailed definitions and a historicized grounding that gives a thorough account of feminist theory's involvement in Romantic studies and provides a rigorous methodology for students to follow, concluding with a highly instructive case study on Jane Austen. Subsequent chapters deal with women and revolutionary politics, the Gothic genre and domestic politics, women and thought, and women and identity, which covers visuality in Romantic texts. Further reading is listed at the end of each chapter. The book includes key illustrations and a comprehensive bibliography.